Optimization of operating parameters of a ground coupled heat pump system by Taguchi method - Esen, Hikmet; Turgut, Emre (Elsevier Science Sa, 2015)
This paper focuses on optimization of vertical ground coupled heat pump (VGCHP) system. This optimization is realized by examining effects of parameters on the system. Thus, experimental studies have been conducted under varying depth of boreholes and temperatures of condenser and evaporator. Then, the Taguchi method is applied to these parameters to optimize coefficient of performance (COP) of VGCHP system. Also, analysis of variance (ANOVA) and signal/noise (S/N) ratio are used for evaluation of experiment results. It is found that depth of borehole is the most significant parameter, affecting the COP by 67.77%. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Optimization; Depth; Ground coupled heat pump; Vertical; Taguchi method